Image-Guided Therapy Systems. - Vaezy, Shahram (Artech House engineering in medicine & biology series., 2009)
This title provides a global survey of the rapidly growing field of image-guided therapy. You find detailed coverage of a wide range of key topics, from MRI-guided surgery, robotic cardiac surgery, and brachytherapy and hyperthermia for cancer treatment . to modern procedures in neurosurgery, laser cosmetic therapy, and ultrasound-guided high intensity focused ultrasound therapy for non-invasive tumor treatment. You learn the fundamentals of imaging and therapeutic modalities and their capabilities and constraints in implementation of image-guided therapy systems.